HUBUNGAN PENGETAHUAN DAN SIKAP PASANGAN USIA SUBUR (PUS) DALAM PENGAMBILAN KEPUTUSAN MENJADI AKSEPTOR KELUARGA BERENCANA - Siti Nur Asyah Jamillah Ahmad; Endah Dwi Pratiwi; Dina M.S Henukh (Jurnal Ilmiah Citra Kebidanan, 2026)
Based on 2024 data in East Nusa Tenggara Province, family planning (KB) utilization was recorded at 40.73%, while in Kupang Regency, the recorded figure was 35.76%. This study aims to analyze the relationship between the knowledge and attitudes of Couples of Childbearing Age (PUS) and their decision-making to become family planning acceptors in Penfui Timur Village. This research employed a quantitative type with a cross-sectional study design. The population in this study consisted of Couples of Childbearing Age (PUS) in Penfui Timur Village. A sample of 100 respondents was selected using a non-probability sampling technique with a purposive sampling approach. Data collection was carried out using a structured questionnaire that had been tested for validity and reliability. Data analysis involved univariate and bivariate analyses using the Chi-Square statistical test and Prevalence Odds Ratio (POR). The Chi-Square test results revealed a significant relationship between knowledge and KB decision-making ($p = 0.000$, POR = 2.725; 95% CI = 2.068–3.592), as well as a significant relationship between attitude and KB decision-making ($p = 0.021$, POR = 1.756; 95% CI = 1.008–2.430). Knowledge is the most dominant factor influencing PUS in practicing family planning at the study site. PUS with poor or moderate knowledge are 2.72 times more likely to not practice family planning, while those with negative attitudes are 1.75 times more likely to refuse to become acceptors.